Autonomic regulation in different hypertensive phenotypes - the HELIUS study - D. Collard; E.M.C. Vriend; H. Galenkamp; E.P. Moll van Charante; L. Vogt; B.E. Westerhof; B.J.H. van den Born (Blood Pressure, 2023)
Background: Hypertension can be classified into different phenotypes based on systolic and diastolic blood pressure (BP) that carry a different prognosis and may therefore be differently associated with sympathetic activity. We assessed the association between cardiac autonomic function determined from continuous finger BP recordings and hypertensive phenotypes. Methods: We included 10,221 individuals aged between 18-70 years from the multi-ethnic HELIUS study. Finger BP was recorded continuously for 3-5 minutes from which cross-correlation baroreflex sensitivity (xBRS) and heart rate variability (HRV) were determined. Hypertension was classified into isolated systolic (ISH; ≥140/<90), diastolic (IDH; <140/≥90) and combined systolic and diastolic hypertension (SDH; ≥140/≥90). Differences were assessed after stratification by age (younger: ≤40, older: >40 years) and sex, using regression with correction for relevant covariates. For xBRS, values were log-transformed. Results: In younger adults with ISH, xBRS was comparable to normotensive individuals in men (ratio 0.92; 95%CI 0.84-1.01) and women (1.00; 95%CI 0.84-1.20), while xBRS was significantly lower in IDH and SDH (ratios between 0.67 and 0.80). In older adults, all hypertensive phenotypes had significantly lower xBRS compared to normotensives. We found a similar pattern for HRV in men, while in women HRV did not differ between phenotypes. Conclusions: In younger men and women ISH is not associated with a shift towards increased sympathetic control, while IDH and SDH in younger and all hypertensive phenotypes in older participants were associated with increased sympathetic control. This suggests that alterations in autonomic regulation could be a contributing factor to known prognostic disparities between hypertensive phenotypes.